2017
DOI: 10.1016/j.kint.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin alters renal calcium and phosphate excretion through regulation of klotho expression

Abstract: The kidney controls systemic calcium and phosphate levels and disturbances of its control mechanisms can lead to a variety of diseases. The insulin-sensitizing adipokine adiponectin is renoprotective and accelerates functional recovery following renal injury. However, unlike other adipokines, adiponectin is reduced in obesity. High adiponectin levels are also correlated with bone loss, suggestive of an additional action in mineral metabolism. Using knockout, wildtype, and adiponectin overexpressing transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 47 publications
4
45
0
1
Order By: Relevance
“…The reasons for this phenomenon are currently unknown. Tan et al showed that Klotho concentrations were not related to the reduction of immunosuppression or to biochemical blood parameters, and, therefore, suggested non-renal related causes of the increased Klotho concentrations (Tan et al 2017). In our study, we also found the Klotho concentrations to be highest in patients after kidney transplantation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The reasons for this phenomenon are currently unknown. Tan et al showed that Klotho concentrations were not related to the reduction of immunosuppression or to biochemical blood parameters, and, therefore, suggested non-renal related causes of the increased Klotho concentrations (Tan et al 2017). In our study, we also found the Klotho concentrations to be highest in patients after kidney transplantation.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies reported that high concentrations of adiponectin were negatively correlated with bone density (Naot et al 2017). Recent animal studies confirmed the ability of adiponectin to reduce Klotho secretion by renal tubular cells and, therefore, confirmed the influence of adiponectin on the regulation of bone mass (Rutkowski et al 2017). Leptin can directly stimulate bone cells to form bone tissue (Cornish et al 2002).…”
Section: Discussionmentioning
confidence: 75%
“…In rats with kidney function disorder model all the cytokines have elevated levels (p<0.05). These data correlate with literature [4][5][6][7]. Analysis of their interrelations showed that in the intact rats it was no correlation between adiponectin and visfatin levels, weak positive correlation between adiponectin and IL-17 and weak negative correlation between visfatin and IL-17 was shown.…”
supporting
confidence: 90%
“…Genotyping was performed as described. 45 Podocyte apoptosis was induced by injection of the dimerizer AP20187 (#635058; Takara, Saint-Germainen-Laye, France). Transgenic male FVB mice aged 8 weeks were injected intraperitoneally with a single dose of 0.5 μg/g body weight of dimerizer 44 or equal volume of vehicle and euthanized after 3 or 7 days.…”
Section: Pod-attac Micementioning
confidence: 99%